Democracy, sovereignty, and security: understanding the normative approaches of third parties involved in the conflicts in Moldova and Ukraine - Albulescu, Ana Maria (Frontiers in Political Science, 2023)
This article compared the process of political settlement in Transnistria and the Donbass region. This comparison ultimately serves toward understanding the following question: What constitute the fundamental differences between historical interpretations of the principles of international order by external parties involved in the design of peace agreements in Moldova and Ukraine and how did this influence their implementation? In analyzing this complex context, this article therefore looks at two major proposals for political settlement in Transnistria—the Kozak Memorandum (2003) and the Yushchenko plan (2005) and the Minsk Agreements (2014/2015) in the Donbass. It focuses on the interpretation of the principles of democracy, sovereignty, and security that have been included in the design of these externally sponsored peace agreements toward providing a conceptual framework for understanding the broader normative approaches of third parties involved in the conflicts in Moldova and Ukraine. It informs an analysis of the role of peace and democracy as foundations of the Liberal International Order.